The Utilization of a TSR-MPPT-Based Backstepping Controller and Speed Estimator Across Varying Intensities of Wind Speed Turbulence - Elzein, I. M.; Maamar, Yahiaoui; Mahmoud, Mohamed Metwally; Mosaad, Mohamed I.; Shaaban, Salma Abdelaal (International Journal of Robotics and Control Systems, 2025)
Because wind systems are so prevalent in the electrical grid, an innovative control method can significantly increase the productivity of permanent magnet synchronous generators (PMSG). A wind power generation system's maximal power point (MPP) tracking control approach is presented in this paper. The nonlinear backstepping controller, which is robust to parameter uncertainty, is used in this work to enhance the tip speed ratio approach.  To lower the system's equipment and maintenance costs, we suggested utilizing a speed estimator. As a novel addition to the backstepping controller development, the suggested estimator is a component of the backstepping controller development. The control and system organization approaches are presented. Lyapunov analysis is used to guarantee the stability of the controller. To assess the suggested approach, step change and varying wind speed turbulence intensities are employed. The results expose the great efficiency of the proposed method in both tracking MPP and calculating generator speed.  The proposed control strategy and structure are validated by MATLAB simulations.